Design and simulation of silicon photodiodes for silicon-based optical receivers - Ei Mon Than (2010)
In the last decade, the speed of microprocessors has been increasing exponentially with time. Therefore, data communication channels will become the speed-bottle-neck in future. The wired electrical connection is used for short and medium distance (centimetres up to hundreds of meters) data communication channels. However, poor impedance matching at high speed results in distorted signals and losses due to the skin-effect. Thus, the electrical wires can be replaced by optical fibres in order to increase the data rate. Due to the low- cost requirement for receiver, the optical detector should preferably be fully implementable in CMOS technology.